How to succeed at the medical interview - Smith, Chris, 1976- (Wiley-Blackwell, BMJ Books, 2013)
Details the types of questions that will be asked at medical interviews and also provides improved guidance for overseas doctors and healthcare professionals and for those seeking to practice abroad.